Cloning and expression of a distinctive class of self-incompatibility (S) gene from Papaver rhoeas L. - Foote, H C (1994)
We present the identification, cloning, and characterization of a self-incompatibility (S) gene from Papaver rhoeas that has no significant homology to any previously reported gene sequences, including S genes from other species. This result suggests that a different self-incompatibility mechanism may be operating in this species and has important implications for the evolutionary relationships between the S genes. The S1 cDNA was cloned by using an oligonucleotide based upon N-terminal amino acid sequence data from stigmatic proteins that show complete linkage with the S1 gene. The single-copy gene has been expressed in Escherichia coli to test biological activity. Although the recombinant S1 protein (S1e) is not processed in the same way as the protein produced in the plant, it exhibits, in vitro, the specific pollen inhibitory activity expected of an S gene product; pollen carrying the S1 allele is inhibited, whereas pollen not carrying S1 is not inhibited. These results provide definitive demonstration that the product of a cloned S gene has S-specific pollen inhibitory activity.